Text-based negotiated interaction of NNS-NNS and NNS-NS dyads on Facebook. Issue 3 (15th June 2017) - Liu, Sarah Hsueh-Jui
Abstract: This study sought to determine the difference in text-based negotiated interaction between non-native speakers of English (NNS-NNS) and between non-native and natives (NNS-NS) in terms of the frequency of negotiated instances, successfully resolved instances, and interactional strategy use when the dyads collaborated on Facebook. It involved 10 native English speakers and 30 learners of English as a foreign language (EFL). NNS-NNS dyads consisted of five H-H pairs and five L-L pairs (H and L representing high- and low-proficiency learners). Similarly, NNS-NS dyads comprised five H-N pairs and five L-N pairs (N being native speakers). All dyads were required to use text chats to complete the given reading tasks synchronously in chatrooms on Facebook. The results suggested that negotiated instances, successfully resolved instances, and interactional strategy use occurred more frequently in H-H pairs than in L-N, L-L, or H-N pairs. In terms of strategy use, H-H, H-N, and L-N dyads were likely to engage in negotiated interaction by employing strategies such as clarifying unclear expressions or checking their comprehension, while L-L used interactional mechanisms infrequently and tended to use strategies such as continuers and asking for assistance. The research concludes with the pedagogical implications of the results.